Real-time image encryption and decryption methods based on the Karhunen-Loeve transform. (8th November 2019) - Rashaideh, Hasan; Shaheen, Ahmad; Al-Najdawi, Nijad
There is always a need for a reliable, fast, and accurate encryption algorithm where marginal concessions are not acceptable. The choice of encrypting images in the frequency domain is more suitable as the image components are de-correlated, which provides a suitable platform to classify those values according to their significance. In this work and based on the Karhunen-Loeve transform and the advanced encryption standard algorithm a symmetric lossless encryption and decryption algorithms are proposed. The proposed encryption scheme is applicable for applications that require protected delivery of high-quality data. In terms of quality, the proposed decryption algorithm outperforms the rest of the algorithms in this domain by providing lossless decrypted images that are identical to the originals. Moreover, well-known statistical tests and security measures have been performed in order to validate the security of the proposed encryption algorithm, the results outperform the state-of-the-art algorithms in this domain.